PEMBINAAN KESADARAN HUKUM DAN HAK POLITIK TERHADAP WARGA BINAAN BAPAS II BUKITTINGGI - Riyanda, Riko; Arman, Zuhdi; Haskar, Edi; Jannah, Miftahul (ASOSIASI IDEBAHASA KEPRI, 2024)
The mentoring process carried out for correctional clients at the Class II Bukittinggi Correctional Center has one aim so that correctional clients can return to society well and not repeat criminal acts. This socialization provides understanding and knowledge for the residents of Bapas II Bukittinggi to obey and adhere to legal awareness and exercise their political rights in public spaces, especially during elections. To support this, the participation of universities is needed to carry out outreach to the community. Therefore, this activity will be beneficial to support government programs in increasing public legal awareness so that they do not repeat criminal acts and obey the law with full responsibility. In politics, citizens who participate actively in elections help overcome election fraud and elect leaders of quality and integrity.